SOFT ISOMORPHISM THEOREMS FOR SOFT HEMIRINGS - Zhu, Kuanyun; Zhan, Jianming (Italian Journal of Pure and Applied Mathematics, 2015)
In this paper, the concepts of soft strong h-ideals and strong h-idealistic soft hemirings are introduced. Some properties of soft hemirings and strong h-idealistic soft hemirings are given. In particular, we construct a novel soft quotient structure of an idempotent hemiring. By means of a kind of new way, soft isomorphism theorems of soft hemirings are established, which are different from soft isomorphism theorems of soft rings.